2004
DOI: 10.1080/j.1440-1614.2004.01485.x
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Lifestyle Factors and Mental Health Measures Among Community-Dwelling Older Women

Abstract: The results of this study are consistent with the hypothesis that depression is directly associated with heavy smoking and inversely associated with physical activity. They also support the idea that non-harmful alcohol consumption is associated with better cognitive performance. Randomised clinical trials should be now designed to clarify whether management of lifestyle factors reduces the incidence of mood disorders and cognitive impairment in later life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 55 publications
(68 reference statements)
4
54
0
2
Order By: Relevance
“…Our study reveals several interesting findings in this regard. Firstly, people with anxiety were significantly either smoker or ex-smoker, which is consistent with the results of recent research which showed similar results (Cassidy et al 2006). Secondly, people with depression or anxiety are more likely than those without these diagnoses to be obese or overweight.…”
Section: Discussionsupporting
confidence: 81%
“…Our study reveals several interesting findings in this regard. Firstly, people with anxiety were significantly either smoker or ex-smoker, which is consistent with the results of recent research which showed similar results (Cassidy et al 2006). Secondly, people with depression or anxiety are more likely than those without these diagnoses to be obese or overweight.…”
Section: Discussionsupporting
confidence: 81%
“…Specifi c questionnaires were developed for some studies but their psychometric properties were not reported. 7,17,28,36 The SF-36 was the most commonly used QoL questionnaire, which corroborates previous reports in the literature. 14 This can be attributed to longer experience using SF-36 since its was developed in the early 1990s 50 while the WHOQOL was developed in the late 1990s.…”
Section: Discussionsupporting
confidence: 76%
“…The lack of evidence reported here for an association between childhood or adulthood folate intake and psychological distress in women at age 53 is consistent with some other studies of the general population, where folate deficiency was not found to be related to depression in women or men in the community (3,4,44,45) . However, other research has suggested that folate may be related to severe depression (46,47) .…”
Section: Comparisons Of Findings With Other Studiessupporting
confidence: 92%